GANTI RUGI DALAM PENYELESAIAN SENGKETA ANTARA JAMAAH UMROH DENGAN PT FIRST TRAVEL ATAS KEGAGALAN PEMBERANGKATAN UMROH - ayu puspita, lita; Setiyadi, Tri (Yustitia, 2020)
This research is based on the reality that occurs in the community that PT First Travel as the organizer of the Umrah pilgrimage trip (PPIU) violates Law Number 8 of 1999 and Regulation of the Minister of Religion Number 8 of 2018 so that it has resulted in losses to consumers of Umrah pilgrims. . PT First Travel does not carry out its obligations as a business actor and does not fulfill the consumer rights of the Umrah pilgrims. The legal relationship that begins with the sale and purchase agreement for Umrah travel services, consumers will depart as promised by PT First Travel, namely 6 months after payment is paid. However, this agreement was denied by PT First Travel so that they must be responsible for compensation to consumers for negligence and mistakes that resulted in the congregation failing to leave for Umrah. In this study, the method used in this case is the Normative Juridical approach method with data collection techniques by means of literature studies on legal materials, both primary legal materials, secondary legal materials and tertiary legal materials and field studies as a complement. The results of this study indicate that the responsibility of PT First Travel which is regulated in Law Number 8 of 1999 concerning Consumer Protection in providing compensation and / or compensation to consumers of Umrah pilgrims is not carried out by PT First Travel, and legal remedies are carried out in practice that occurred in the field of Umrah congregation consumers in defending their right to receive compensation ended in dispute resolution by filing a civil suit with the Depok District Court.